To use or not to use, that is the question: On students’ encounters with a library of examples - Greensfeld, Hava (Cogent social sciences, 2017)
Understanding learning processes in an example-based environment is of interest to scholars from various disciplines. This qualitative study presents the missing perspective: the emotional and motivational aspects that accompany learning in an example-based environment. The participants of our study were 70 students in four classes (2010-2013) of “The Learning Processes,” an academic course at a teacher-education college. Research tools were: An open questionnaire to expose the students’ preconceptions regarding the use of a library of examples in learning processes, three reflective journals, observations, and a designated library of examples. In this study we adopted a unique pedagogical strategy, both in constructing the library of examples and in determining when the examples would be studied. Content analysis revealed two contrasting approaches : the “objecting” versus the “agreeing”; these led to identification of six academic emotional types (three “objecting” types and three “agreeing” types) of users of the example-based environment. The processes that caused each student to behave in a particular way were found to be complex, with external-behavioral expressions (actual use of examples), and internal expressions. These were related to each type’s focused achievement goal, academic self-concept, and to social-academic emotions aroused in this environment. The present study broadens the implications of the theory of learning through examples, and emphasizes the widely varied preferences of learners in a an example-rich environment.